The Economist: Business Consulting: A Guide to How it Works and How to Make it Work - Fiona Czerniawska; Gilbert Toppin (London The Economist, 2005)
The ultimate guide for those using or planning to use business consultants - and for consultants themselves In the last three decades of the 20th century the management consultancy industry grew at a cracking pace but increased scepticism about the value that consultants genuinely add, combined with the economic slowdown, has made life much tougher for the consulting industry. As firms have cut back on consulting services and begun to review the way they use consultants, consulting firms themselves are looking at how they need to change. People are now talking about business consulting rather than management consulting. Using real examples from a range of private sector firms, public sector organisations and from the consultants themselves, this book explores the new business consulting world and looks at every element of it with the aim of both helping firms make better use of consultants and showing consultants how they need to adapt and provide their clients a better service.
Keywords: Nonfiction; Business; Enterprise and Practice (BIN2045-N)